The congruence opinion as coordination mechanism in Mexican urban law - Jiménez Dorantes, Manuel (Universidad Nacional del Litoral, 2020)
In Mexico, the land use law prescribes that the States issues the congruence opinion about urban planning of the local government. The weak legal configuration leaves open the possibility of excessive interference by state authority in the urban model approved by the local government. This work exposes the places of risk for the local authority and provides a solution or approach to limit the possibilities of the congruence opinion.